Contextual auditory processing in the inferior colliculus is affected in a sex- and age-dependent manner in the valproic acid-induced rat model of autism. - Sara Cacciato-Salcedo; Ana B Lao-Rodríguez; Manuel S Malmierca (PLoS Biology)
Diverse biological factors, such as sex and age, confer heterogeneity on sensory processing challenges in autism. These factors result in major difficulties in the processing of contextual information in social and non-social situations. To assess divergence in autistic traits, it is critical to consider sex- and age-related variability. Nevertheless, these differences remain largely elusive. Animal models of autism offer the possibility to examine contextual processing at the single-neuron level. Here, we investigated predictive processing of contextual auditory cues in the auditory midbrain of control and prenatally valproic acid-induced rats, a well-established animal model of autism. The rats were prepubertal and adult female and male animals. We performed single-unit recordings in the inferior colliculus of control and prenatally, or in utero, exposed rats under the classical oddball paradigm and non-repetitive cascade control sequences to study neuronal mismatch. This is the neuronal correlate of mismatch negativity, the brain's automatic response to interruptions in environmental regularity. When comparing control and exposed rats, our results demonstrated a reduction in neuronal mismatch in rats exposed to valproic acid. However, exposed adult females exhibited an increased neuronal mismatch compared to their control counterparts. With respect to sex distinctions, valproic acid induced sex differences in neuronal mismatch of prepubertal and adult rats that are not observable in control animals. Moreover, we detected an age-dependent refinement in prediction error that is not affected by the drug. But valproic acid altered typical developmental trajectory of neuronal mismatch in both sexes. Such observations support sex- and age-related effects of in utero valproic acid exposure in contextual auditory processing at the neural level of the inferior colliculus. In autism, atypical predictive processing of environmental regularities underlies unusual responses to novel experiences. The present study highlights the importance of sex and age, that confer heterogeneity to these challenges.